DECISION OF THE USE OF DEBT TO INCREASE PROSPERITY OF COMPANY OWNER IN FOREIGN COMPANY AND DOMESTIC COMPANY ON INDONESIAN STOCK EXCHANGE - Susanti Susanti; Edi Pranyoto (Proceeding International Conference on Information Technology and Business, 2016)
The capital structure is a combination of debt and equity that was used by the company. Differences in capital structure, decision-making are influenced by the type of the company, whether the company is Foreign or Domestic. The Foreign company, majority shareholders are foreigners, in addition, most management using foreign management. This is the opposite of the Domestic company, if the Domestic company, majority shareholder is a person or agency that originated from within the country and management is the management in the country. The company's debt usage decision characteristic of Foreign and Domestic companies can be seen from Debt to Equity Ratio (DER), it will have an effect on the prosperity of the company's share owners. Based on the results of the analysis, show that Debt to Equity Ratio in the Foreign and Domestic company have the same height. The average DER of Foreign company was 85,1467 percent and DER of Domestic company was 86,8667 percent. While the prosperity company owner can be seen since Return on Equity (ROE) in the Foreign company since that Domestic company. The average ROE of Foreign company was 37,75093 percent and ROE of Domestic company was 20,53147 per cent. Based on the test results shown that there is a difference in impact in the use of debt (DER) to the financial performance (ROE) between Domestic and Foreign company. The difference is seen from the two companies, the elasticity of the visible that ROE of Foreign company is more sensitive to changes cause DER than Domestic company. Key Words: Capital Structure, Debt, Equity